Transcriptome-wide elucidation of liposomal formulations for anticancer drug delivery - Huang, Bu-Wei (2018)
Although widely used in chemotherapy, free doxorubicin (Dox) might enhance cell malignancy undesirably. Liposomal Dox (Doxlipo) has been clinically approved for the treatment of breast cancer due to reduced systematical toxicity and increased tumor targeting, yet the transcriptome-wide elucidation of the Doxlipo formulations remains elusive. To this end, we explored the impact of two Dox liposomal formulations, Doxlipo mainly containing hydrogenated soy phosphatidylcholine or 1,2-dipalmitoyl-sn-glycero-3-phosphocholine, on the transcriptional pattern of MCF-7 cells. The two types of Dox liposomal formulations with different drug release kinetics were investigated to reveal the relationship between the formulation and tumor malignancy. Interestingly, we found that liposomal formulation significantly altered the transcriptional pattern of a wide range of genes. Under equivalent dosage of Dox, free Dox substantially changed the expression of ANK1, ACTA2, GPR87, GDF15, FZD6, and WNT4 in MCF-7 cells. Notably, free Dox induced much higher expression of ABCB1 and significantly enhanced the cell migration behavior in comparison with HSPC Doxlipo under a similar level of cytotoxicity. Finally, siRNA targeting GPR87 was codelivered with cationic Doxlipo to reduce the expression of malignancy-related genes. Our study, for the first time, provides an overview of the influence of formulation on the malignancy at transcriptional level and reveals the relationship between cytotoxicity and cell malignancy from the formulation aspect, offering valuable reference for the future formulation design for anticancer drug delivery.